Painting, Writing and Voice: The Phaedrus between Levinas and Derrida - Cervato, Giulia (Aesthetica Preprint, 2023)
The relationship between orality and writing, especially with respect to their ability to express otherness, was one of the most debated topics in the colloquium between Emmanuel Levinas and Jacques Derrida. To address it, both philosophers could not but independently confront the Platonic Phaedrus, the text that founds this problem within Western philosophical tradition. Both authors’ exegeses focus on the connection determined by Socrates with a third expressive language, the artistic-figurative one, and on the relationship that written speech establishes with its author’s signifying intentionality. Nevertheless, their interpretative outcomes are very distant from each other: this essay aims to keep track of this hermeneutical distance in order to (1) evaluate the dialogue that they autonomously developed with the Phaedrus and (2) let emerge the reason why Levinas’ and Derrida’s thoughts, despite being so kindred, choose two antithetical paths when dealing with this fundamental issue.